Dissecting the role of the germinal vesicle nuclear envelope and soluble content in the process of somatic cell remodelling and reprogramming - Helena FULKA; Atsuo OGURA; Pasqualino LOI; Josef FULKA, Jr (The Society for Reproduction and Development, 2019)
Differentiated nuclei can be reprogrammed/remodelled to totipotency after their transfer to enucleated metaphase II (MII) oocytes. The process of reprogramming/remodelling is, however, only partially characterized. It has been shown that the oocyte nucleus (germinal vesicle - GV) components are essential for a successful remodelling of the transferred nucleus by providing the materials for pseudo-nucleus formation. However, the nucleus is a complex structure and exactly what nuclear components are required for a successful nucleus remodelling and reprogramming is unknown. Till date, the only nuclear sub-structure experimentally demonstrated to be essential is the oocyte nucleolus (nucleolus-like body, NLB). In this study, we investigated what other GV components might be necessary for the formation of normal-sized pseudo-pronuclei (PNs). Our results showed that the removal of the GV nuclear envelope with attached chromatin and chromatin-bound factors does not substantially influence the size of the remodelled nuclei in reconstructed cells and that their nuclear envelopes seem to have normal parameters. Rather than the insoluble nuclear lamina, the GV content, which is dissolved in the cytoplasm with the onset of oocyte maturation, influences the characteristics and size of transferred nuclei.